Characterization of Native and Modified Starches by Potentiometric Titration. (2nd December 2014) - Soto, Diana; Urdaneta, Jose; Pernia, Kelly
Abstract : The use of potentiometric titration for the analysis and characterization of native and modified starches is highlighted. The polyelectrolytic behavior of oxidized starches (thermal and thermal-chemical oxidation), a graft copolymer of itaconic acid (IA) onto starch, and starch esters (mono- and diester itaconate) was compared with the behavior of native starch, the homopolymer, and the acid employed as a graft monomer and substituent. Starch esters showed higher percentages of acidity, followed by graft copolymer of itaconic acid and finally oxidized starches. Analytical techniques and synthesis of modified starches were also described.